The Performance of the Headmaster in Improving the Quality of Education at Madrasah Tsanawiyah Negeri 1 Siak - Maisah Maisah; Yumesri Yumesri; Fadlilah Fadlilah; Husin Husin (Edumaspul: Jurnal Pendidikan, 2024)
This study examines the performance of the headmaster in improving the quality of education at Madrasah Tsanawiyah Negeri 1 Siak (MTsN 1 Siak), with a focus on leadership strategies and their impact on educational outcomes. The research emphasizes the headmaster's role in enhancing both religious and general education, empowering teachers, and providing necessary resources to improve learning experiences. Data was collected through interviews with the headmaster, teachers, and administrative staff, along with direct observations of the school's activities. The findings highlight the headmaster's efforts to implement strategic programs, such as professional development for teachers, tutoring for students, and improving school infrastructure. Despite facing challenges like limited facilities and competition from other schools, the headmaster's leadership has positively impacted student learning outcomes, teacher motivation, and the school's reputation. The study concludes that the headmaster's transformational leadership and commitment to education quality have been pivotal in driving improvements at MTsN 1 Siak.